Meso-scale Order Structure Prepared From Immiscible Polymer Blend Solutions. Issue 1663 (13th March 2014) - Jang, Junhyeok; Inoue, Tsuyoshi; Kawazoe, Masayuki; Yoshida, Hirohisa
ABSTRACT: The meso-scale hexagonally packed order structures were obtained by solvent casting from the immiscible polymer blend solutions. The order structures were the result of phase separation occurred at the evaporation front during the solvent casting, the so-called dissipative system. The order domains were flat spheres or ellipses on the matrix surface depending on the combination of polymer blends and solvent, the diameter of spheres were tunable from 0.5 to 3 μm by the casting condition, such as the solvent used for mixing and the evaporation rate. Three blend systems, NBR/SBR, NBR/BR and PMMA/BR, formed two dimensional order structures with the domain size in μm-scale by solvent casting from those homogeneous solutions. The conditions to obtain the two dimensional meso-scale order structure were evaluated.